Instilling Students’ Character Values Through Morals Education Using an Affective Approach at MAS 01 Darussalam Kepahiang - Yupande, Putra; Nurlaili, Nurlaili (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
The aim of this study is to analyze affective-based moral education strategies in instilling character values among students at MAS 01 Darussalam Kepahiang. The research employed a descriptive qualitative approach, using in-depth interviews, participant observation, and documentation for data collection. The study was conducted at MAS 01 Darussalam Kepahiang, a private Islamic senior high school in Kepahiang Regency, Bengkulu Province. The results revealed that the moral education strategy at this school emphasizes an affective approach, focusing on shaping students' attitudes, emotions, and moral awareness. Through this approach, students gain moral knowledge and internalize character values through emotional experiences. Key strategies include teacher role modeling, habituation of positive behavior, value reflection, and recognition for good behavior. In conclusion, this approach has proven effective in fostering character development and creating a deep moral awareness.